Música e audição: os sentidos atribuídos por Disc Jockeys de música eletrônica - Lopes, Juliana Julio (2009)
Disc Jockeys are music professionals exposed to high sound pressure levels during the working day. Several studies were carried out showing the impacts of such professional activity in hearing, however, none was directed to understand the meaning of music and hearing assigned by Disc Jockeys. Purpose: To study the meaning of music and hearing assigned by Disc Jockeys and the possible implications of these professional activity on the hearing health . Method: Descriptive, analytical, and qualitative research in which four Disc Jockeys were interviewed, all male, aged between 26 and 34 years, working with electronic music for at least a year in the region of greater São Paulo. It was direct interviews composed by four questions: (1) What music means or represents in your life? (2) What electronic music means or represents in your life? (3) How is your hearing in that context? (4) Do you notice any changes related to the hearing after having commenced this activity as a Disc Jockey? To reach the meaning the interviews were transcript and analyzed by the categorization method proposed by Bardin (2009). Results: The discourses showed tree categories: (1) Representation of music ; (2) Representation of hearing and (3) Changes in hearing after performing as Disc Jockey . The main meaning attributed to "music" was to move the emotions. The meaning attributed to "hearing" and to "changes in hearing after performing as Disc Jockey" was to evolve, because hearing is a tool for listening and imagination, which allows learning. Final considerations: As to categories (2) and (3) was only given the meaning of evolution and never of loss of hearing, we concluded that: 1 to perform as a Disc Jockey has only a positive implications to health, 2- the interviewed DJs don t know the risks of excessive exposure to intense sound levels; 3 - speech and hearing work is important for the group of the studied professionals; 4 - further research is needed to know whether these absence of knowledge is extensible to the group of Disc Jockeys. This research is important to develop adequated heath action in the speech and hearing field